Rough Multilinear Fractional Integrals on Weighted Morrey Spaces - Xiao Li; Runqing Cui (Journal of Function Spaces)
It is showed that a class of multilinear fractional operators with rough kernels, which are similar to the higher-order commutators for the rough fractional integrals, are bounded on the weighted Morrey spaces.